2003
DOI: 10.1097/01.brs.0000085356.89103.a5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Study of the Morphology of Human Cervical Facet Joint

Abstract: Facet joint morphology varies with the regions of the cervical spine (upper vs. lower), gender (male vs. female), and location (dorsal vs. ventral). Because of the lack of intervertebral discs in the UCS region, variations in these geometrical characteristics affect the biomechanical behaviors of the human spine secondary to external loads. Furthermore, the lack of adequate cartilage in females may expose the underlying adjacent subchondral bone to direct stresses during normal physiologic and traumatic loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 24 publications
2
52
0
1
Order By: Relevance
“…Further, reports have found that the bony extremity of the pillars is not always completely covered by a cartilage layer, leaving a region of exposed subchondral bone at the outermost edges of the bony pillar [19,41]. Yoganandan et al [19] reported the gap of exposed subchondral bone to be nearly three times wider in the upper region of the cervical spine than in the lower cervical spine, especially in the posterior and anterior regions of the facet articulating surfaces. The cartilage layer may be thinner in these regions because of the presence of synovial folds and meniscoids, which also provide additional protection from compressive and shear loads across the joint (see Sec.…”
Section: Cartilaginous Articularmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, reports have found that the bony extremity of the pillars is not always completely covered by a cartilage layer, leaving a region of exposed subchondral bone at the outermost edges of the bony pillar [19,41]. Yoganandan et al [19] reported the gap of exposed subchondral bone to be nearly three times wider in the upper region of the cervical spine than in the lower cervical spine, especially in the posterior and anterior regions of the facet articulating surfaces. The cartilage layer may be thinner in these regions because of the presence of synovial folds and meniscoids, which also provide additional protection from compressive and shear loads across the joint (see Sec.…”
Section: Cartilaginous Articularmentioning
confidence: 99%
“…An avascular layer of hyaline cartilage, with varying thickness across spinal regions and the genders, covers the articulating surfaces of each facet [19,40]. The cartilage is thinner at the edges of the opposing surfaces and gradually increases to its thickest ($1 mm) towards the center of the articulating joint, in both the antero-posterior and medio-lateral regions of the joint [41].…”
Section: Cartilaginous Articularmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,6,17) However, few studies have considered the cervical facet joint. 10,16,23) The mechanism underlying the formation of a hypertrophic synovial mass remains to be elucidated. The present and previous cases of hypertrophic synovial mass arose from a facet manifesting degenerative changes, and the histological diagnoses were proliferated fibrous connective tissue that appeared to be formed by mechanical stress between the articular surfaces.…”
Section: Discussionmentioning
confidence: 99%